Virtual Screening of Sulphonyl Urea Derivative and In-silico, In Vitro Anticoagulant Evaluation of Lead Molecules - K. Chaithanya Veena (Journal of Global Pharma Technology, 2018)
Objective: The objective of present study is the virtual screening of sulphonylurea analogues followed by the insilico and in vitro evaluation for its anticoagulant activity. Method and result: the method of virtual screening selected is the structure based virtual screening using Ch EMBL database. The in silico analysis was performed using auto dock tools 4.2.The docking was performed using 1TA2 (thrombin) and 1FJS(clotting factor Xa) as the binding proteins which are drawn from the protein data bank. The sulphonyl urea analogues obtained from virtual screening are allowed to dock with the clotting proteins, the binding energies and docking positions were determined using auto dock tools 4.2.the in vitro evaluation of anticoagulant activity were performed, the prothrombin time(PT) and activated thromboplastin time(APTT) were determined. Conclusion: The sulphonylurea analogues are capable of producing the anticoagulant activity. Keywords: Virtual screening, Sulphonyl urea analogues, Anticoagulant activity, Gliclazide, glimepiride, War far in, In silico analysis.